The Involvement of Post-Translational Modifications in Alzheimer's Disease - Marcelli, Serena; Corbo, Massimo; Iannuzzi, Filomena; Negri, Lucia; Blandini, Fabio; Nistico, Robert; Feligioni, Marco (Current Alzheimer Research, 2018)
Background: Alzheimer's disease (AD) is a neurodegenerative disorder recognized as the most common cause of chronic dementia among the ageing population. AD is histopathologically characterized by progressive loss of neurons and deposits of insoluble proteins, primarily composed of amyloid-β pelaques and neurofibrillary tangles (NFTs). Methods: Several molecular processes contribute to the formation of AD cellular hallmarks. Among them, post-translational modifications (PTMs) represent an attractive mechanism underlying the formation of covalent bonds between chemical groups/peptides to target proteins, which ultimately result modified in their function. Most of the proteins related to AD undergo PTMs. Several recent studies show that AD-related proteins like APP, Aβ, tau, BACE1 undergo post-translational modifications. The effect of PTMs contributes to the normal function of cells, although aberrant protein modification, which may depend on many factors, can drive the onset or support the development of AD. Results: Here we will discuss the effect of several PTMs on the functionality of AD-related proteins potentially contributing to the development of AD pathology. Conclusion: We will consider the role of Ubiquitination, Phosphorylation, SUMOylation, Acetylation and Nitrosylation on specific AD-related proteins and, more interestingly, the possible interactions that may occur between such different PTMs.
Keywords: Acetylation